1999
DOI: 10.1071/wr97061
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, habitat and conservation status of the rare dusky hopping-mouse, Notomys fuscus (Rodentia : Muridae)

Abstract: The distribution, habitat and conservation status of Notomys fuscus were determined by collating past records of the species and conducting field investigations covering areas of historical distribution and similar habitats. Detailed population sampling was carried out in two geographically distinct locations where populations appeared to be extant. Evidence of N. fuscus was found throughout the Strzelecki Desert east and south of the Strzelecki Creek in South Australia and in an isolated group of dunes south-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Sand dune habitat appears critical for sustaining hopping-mice populations given that their presence declined as the height and density of sand dunes likewise declined ( Fig. 3; see also Moseby et al, 1999). Hopping-mice population trends fluctuated independent of dingo control ( Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sand dune habitat appears critical for sustaining hopping-mice populations given that their presence declined as the height and density of sand dunes likewise declined ( Fig. 3; see also Moseby et al, 1999). Hopping-mice population trends fluctuated independent of dingo control ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…foxes, cats and rabbits). The Strzelecki Desert is the last stronghold of hopping-mice (Lee, 1995;Moseby et al, 1999;Van Dyck and Strahan, 2008), which are an endangered, 'old world' or conilurine rodent (Muridae) with irruptive population cycles typical of many small mammals in arid areas.…”
Section: Introductionmentioning
confidence: 99%
“…Where their distributions overlap, the differing habitat preferences of hopping-mouse species may facilitate sympatricity by reducing competition for resources (Moseby et al 1999;Watts and Aslin 1981). Habitat partitioning with other rodent species may also occur at the microhabitat scale.…”
Section: Distribution Habitat and Population Driversmentioning
confidence: 99%
“…Notomys cervinus is found on sparsely vegetated gibber plains and clay plans of the Lake Eyre Basin and may utilise pockets of sandy substrates for burrow construction (Breed and Ford 2007;Breed 2008). Notomys fuscus is patchily distributed across a variety of sand dune habitats of the Strzelecki Desert (Moseby et al 1999) and has been observed to utilise or traverse clay pans (Moseby et al 2006). Notomys mitchelli occurs across much of southern Australia's mallee and heath country with deep sandy soils Watts and Aslin 1981).…”
Section: Distribution Habitat and Population Driversmentioning
confidence: 99%
See 1 more Smart Citation